Avenger in distress: a semiotic study of Lisbeth Salander, rape-revenge and ideology. Issue 1 (2nd January 2021) - Fredriksson, Tea
ABSTRACT: Culturally constructed ideals and stereotypes are part of collective sense-making processes. One such stereotype is Nils Christie's ideal victim. The present study discusses how the ideal victim shares key features with another cultural stereotype: the damsel in distress. Moreover, the study addresses attempts at subverting such stereotypes, which can be found in the women avengers of rape-revenge narratives. Studies of rape-revenge narratives have elucidated how such stories (re)imagine rape victimhood and survival in Western and Nordic culture, in ways that question the ideal victim qua damsel and her underlying patriarchal ideologies from a feminist perspective. However, such critique has led to the creation of other stereotypes and ideologically complex and even problematic portrayals of rape and victimization. Through a semiotic analysis of portrayals of a popular rape-revenge protagonist, Lisbeth Salander, the present study discusses how different ideologies surface, converse, and collide in fictional narratives of rape, survival, victimhood, revenge, and retribution. The study finds that while embodying resistance to the damsel, Lisbeth Salander also embodies aspects of the patriarchal ideologies that keep the damsel in place, thus creating an ideologically complex image. This creates a space for questioning the cultural understanding of rape, victimhood, and resistance.